Rad51 and Rad54 ATPase activities are both required to modulate Rad51-dsDNA filament dynamics - Li, Xuan (Oxford University Press, 2007)
Rad51 and Rad54 are key proteins that collaborate during homologous recombination. Rad51 forms a presynaptic filament with ATP and ssDNA active in homology search and DNA strand exchange, but the precise role of its ATPase activity is poorly understood. Rad54 is an ATP-dependent dsDNA motor protein that can dissociate Rad51 from dsDNA, the product complex of DNA strand exchange. Kinetic analysis of the budding yeast proteins revealed that the catalytic efficiency of the Rad54 ATPase was stimulated by partial filaments of wild-type and Rad51-K191R mutant protein on dsDNA, unambiguously demonstrating that the Rad54 ATPase activity is stimulated under these conditions. Experiments with Rad51-K191R as well as with wild-type Rad51-dsDNA filaments formed in the presence of ATP, ADP or ATP-γ-S showed that efficient Rad51 turnover from dsDNA requires both the Rad51 ATPase and the Rad54 ATPase activities. The results with Rad51-K191R mutant protein also revealed an unexpected defect in binding to DNA. Once formed, Rad51-K191R-DNA filaments appeared normal upon electron microscopic inspection, but displayed significantly increased stability. These biochemical defects in the Rad51-K191R protein could lead to deficiencies in presynapsis (filament formation) and postsynapsis (filament disassembly) in vivo.